Optimasi ampas jahe merah (Zingiber officinale var rubrum) sebagai essential oils terintegrasi metode eae (enzyme – assisted extraction) dan destilasi fraksinasi: Optimization of red ginger dregs (Zingiber officinale var rubrum) as essential oils integrated with eae (enzyme-assisted extraction) and fractional distillation methods - Chuddin, Miftah; Swasono, Muh. Aniar Hari (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
Ginger dregs left over from processing ginger commodities contain a bioactive compound, namely zingiberene, which has the potential to be used as a functional product in the form of essential oil. The aim of this research was to determine the effect of treatment with variations in cellulase enzyme concentration and duration of enzymatic extraction (Enzyme-assisted extraction) on the yield characteristics, acid number and refractive index of red ginger dregs oil. This research used a factorial group experimental design (RAK) consisting of 2 factorials, namely the concentration of cellulase enzyme powder (1%, 1.5% and 2%) and the duration of EAE (Enzyme-assisted extraction) extraction (130 minutes and 180 minutes) with 3 repetitions, resulting in 6 treatment combinations and 18 experiments.. The analysis carried out in this study was an analysis of the percentage yield of red ginger dregs essential oil and an analysis of the quality including the value of the acid number and refractive index. The results showed that the concentration of the cellulose enzyme with the duration of the EAE extraction produced yield percentages ranging from 19.13% - 38.3%, percentages of acid numbers ranging from 1.25 - 1.93 mgKOH/g and refractive index ranging from 1.08 - 1.30. The effectiveness test showed that the best treatment was achieved by treatment code X2Y3 with a treatment factor (EAE extraction duration of 180 minutes: 2% cellulosic enzyme concentration) with NP parameters (productivity value) yield 0.34, acid number 0.29 and refractive index 0.37.